Dropwise condensation heat transfer process optimisation on superhydrophobic surfaces using a multi-disciplinary approach. (5th August 2016) - Khatir, Z.; Kubiak, K.J.; Jimack, P.K.; Mathia, T.G.
Highlights: Droplets jumping phenomenon can enhance condensate evacuation from the surface. Droplets jumping velocity depends on droplets radius and surface static contact angle. Optimum conditions are for droplets with radius 35–40 μm and contact angle near 160°. Jumping phenomenon occurs only when static contact angle is above 140°. The optimal functional surface design maximises jumping velocity and heat flux. Abstract: Dropwise condensation has superior heat transfer efficiency than filmwise condensation; however condensate evacuation from the surface still remains a significant technological challenge. The process of droplets jumping, against adhesive forces, from a solid surface upon coalescence has been studied using both experimental and Computational Fluid Dynamics (CFD) analysis. Both Lattice Boltzmann (LBM) and Volume of Fluid (VOF) methods have been used to evaluate different kinematic conditions of coalescence inducing a jump velocity. In this paper, an optimisation framework for superhydrophobic surface designs is presented which uses experimentally verified high fidelity CFD analyses to identify optimal combinations of design features which maximise desirable characteristics such as the vertical velocity of the merged jumping droplet from the surface and energy efficiency. A Radial Basis Function (RBF)-based surrogate modelling approach using Design of Experiment (DOE) technique was used to establish near-optimal initial process parameters around which to focus the study. This multidisciplinary approach allows us to evaluate the jumping phenomenon for superhydrophobic surfaces for which several input parameters may be varied, so as to improve the heat transfer exchange rate on the surface during condensation. Reliable conditions were found to occur for droplets within initial radius range of r = 20–40 μm and static contact angle θs ∼ 160°. Moreover, the jumping phenomenon was observed for droplets with initial radius of up to 500 μm. Lastly, our study also reveals that a critical contact angle for droplets to jump upon coalescence is θc ∼ 140°.